ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP LOYALITAS NASABAH (Studi pada Nasabah PT. Bank Mandiri Cabang Pahlawan Semarang) - Prameswari, Dika Sukma (Master of Management Diponegoro University, 2009)
The number of customers of the Mandiri Planned Saving of the Pahlawan Branch of Mandiri Bank who does not proceed with their planned saving is relatively high. The number exceeds 33.6%. This can be an indication that there is a customer loyalty problem in the Pahlawan Branch of Mandiri Bank. Based on the problem, this research is focused on examining the question of â€œHow to improve the loyalty of customer of the Pahlawan Branch of Mandiri Bank?â€The researcher tries to answer the problem through an approach of five variables which are service quality, product quality, customer satisfaction, relationship quality, and customer loyalty. Data of these five variables is collected by distributing questionnaires to 135 customers of PT. Bank Mandiri Cabang Pahlawan Semarang. Then data is analyzed using Structural Equation Modeling (SEM).The test on the five research variables results under the SEM method show that customer satisfaction is significantly affected by service quality and product quality, while the customer loyalty is significantly affected by the customer satisfaction and the relationship quality.Based on the result of data analysis, customer loyalty can be improved through the customer satisfaction by making better the product quality of the Mandiri Planned Saving.